HISTORY OF PEDAGOGICAL THOUGHT AND ISSUES OF TEACHER SKILLS IN SCHOOL PRACTICE, STUDY OF THE TOPIC OF THE MAIN COMPONENTS OF PEDAGOGICAL SKILLS (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This topic covers the formation and stages of development of the issue of teacher skills in the history of pedagogical thought. Based on the pedagogical views of Eastern and Western thinkers, the professional competence, moral qualities and role of the teacher in the educational process are analyzed. Also, the importance of pedagogical skills in school practice, its main components - pedagogical knowledge, pedagogical abilities, communication culture, professional ethics and innovative approaches are studied. The study pays special attention to ways to develop pedagogical skills and issues of increasing the effectiveness of teacher activities.